The Effect of Size, Market Risk, Operational Risk, Liquidity Risk, and Credit Risk on Profitability in Banks in the KBMI 3 AND KBMI 4 Categories For The 2017-2021 - Muhamad Tri Saputro Putro; Nur Hadiyazid Rachman; Ummu Salma Al-Azizah (Asosiasi Dosen Akuntansi Indonesia, 2022)
This study aims to analyze the effect of firm size, market risk, operational risk, liquidity risk, credit risk on banking profitability in the category of KBMI 3 and KBMI 4 for the 2017-2021 period. The method used is quantitative. The data processing technique used Eviews 12, namely statistical analysis and panel data regression analysis. The data is taken from financial reports at OJK and bank websites. The results obtained from this study are that the panel data regression calculation used in this study, the Fixed Effect Model (FEM) is the best model compared to other models. Partially the size value has an influence on profitability, NIM (Net interest Margin) has an influence on profitability, BOPO (Operating Costs and Operating Income) has no effect on Profitability, LDR (Loan To Deposit) has an influence on Profitability, NPL (Non Performing Loans) ) has no effect on Banking Profitability in Indonesia. And simultaneously Size, NIM, BOPO, LDR, NPL have an influence on Banking Profitability in Indonesia.